Success Factors Influencing Food Inspection Management In UAE - Abdulla Almahrooqi, Fahed Khamis; Arif, Sazelin; Zainudin, Mohamad Zahir (International Journal of Sustainable Construction Engineering and Technology, 2022)
Third-party halal certifications are frequently used as the main distribution channels for stunned meat in the UAE and other Muslim societies. Food inspectors are not taught how to interact with these outside parties, which is the main cause of this. This sheds light on the reason why the halal food inspectors were unable to thoroughly check packaged food and certifications. Hence, this paper presents a study on determine the success factors influencing halal food inspection management in UAE. The study identified 48 factors and clustered it into seven groups namely top management commitment; adequate support; halal training and education; employee attributes and management ; policy and procedure ; halal personnel empowerment ; customer focus. These factors were used in the questionnaire development and respondents were request to gauge the influence of these factors based on Likert scale. The data collected from this questionnaire survey was was analysed and found that A total of all of the variables, of which 15 have mean values of 2.68 or higher which are considered as highly influencing factors. In term of the group performance, it was found that the highest group of factors affecting the halal inspection management is halal training and education, followed by top management commitment then by customer focus then by halal personnel empowerment then by adequate support then by policy and procedure and finally by employee attributes and management.